2020
DOI: 10.1093/mnras/staa1877
|View full text |Cite
|
Sign up to set email alerts
|

Wide binaries are rare in open clusters

Abstract: The population statistics of binary stars are an important output of star formation models. However, populations of wide binaries evolve over time due to interactions within a system’s birth environment and the unfolding of wide, hierarchical triple systems. Hence, the wide binary populations observed in star-forming regions or OB associations may not accurately reflect the wide binary populations that will eventually reach the field. We use Gaia DR2 data to select members of three open clusters, Alpha Per, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 94 publications
(140 reference statements)
2
35
0
Order By: Relevance
“…That study found that the rate of wide multiples (between 300 and 3000 au) is higher in young moving groups (14.6%) than in field stars (7.8%) or open clusters (Hyades, 2.5%) which is in agreement with our results (see § 2.2). Deacon & Kraus (2020) concluded that the rate of multiple systems might be influenced more strongly by environmental factors than by age which supports the idea of different formation environments for young moving groups and field stars. It seems that wide separation multiple systems are more effectively formed in less dense regions such as young moving groups.…”
Section: Different Star Formation Environmentssupporting
confidence: 62%
See 1 more Smart Citation
“…That study found that the rate of wide multiples (between 300 and 3000 au) is higher in young moving groups (14.6%) than in field stars (7.8%) or open clusters (Hyades, 2.5%) which is in agreement with our results (see § 2.2). Deacon & Kraus (2020) concluded that the rate of multiple systems might be influenced more strongly by environmental factors than by age which supports the idea of different formation environments for young moving groups and field stars. It seems that wide separation multiple systems are more effectively formed in less dense regions such as young moving groups.…”
Section: Different Star Formation Environmentssupporting
confidence: 62%
“…The third scenario to explain the higher detection rate supposes that the environment of young moving groups is different to that in which field stars form, such that these regions might be more conducive to the retention of bright discs. Deacon & Kraus (2020) analysed the binary fraction of open clusters such as the Pleiades and compared it to less dense associations including the BPMG. That study found that the rate of wide multiples (between 300 and 3000 au) is higher in young moving groups (14.6%) than in field stars (7.8%) or open clusters (Hyades, 2.5%) which is in agreement with our results (see § 2.2).…”
Section: Different Star Formation Environmentsmentioning
confidence: 99%
“…> 5, respectively. We identified companions by applying the method described in Deacon & Kraus (2020), which takes into account the possible orbital motion of the components. We found probable wide separation companions to TYC 4515, TYC 8105, TYC 4946, TYC 4209, and TYC 4479, i.e., to all stars with the exception of TYC 5940.…”
Section: Stellar Companionsmentioning
confidence: 99%
“…However, all of these stars are members of young open clusters (V488 Per: α Per open cluster, HD 23514: Pleiades, P 1121: NGC 2422). By studying wide binary systems in the α Per, Pleiades, and Praesepe open clusters, Deacon & Kraus (2020) demonstrated that at projected separations >3000 au it is difficult to separate true binaries and unrelated cluster members. Although it cannot be completely ruled out that some of the revealed candidates are true binaries, the separations suggest that they instead fall into the latter category.…”
Section: Wide Separation Companionsmentioning
confidence: 99%
“…Under these conditions, it is difficult to see how stellar pairs with separations 0.1 pc can form, let alone survive, in a star-forming environment (see e.g. Scally, Clarke & McCaughrean 1999;Parker et al 2009;Elliott & Bayo 2016;Deacon & Kraus 2020). The obvious alternative is formation via random entrapment of unrelated stars in the field.…”
Section: Introductionmentioning
confidence: 99%